Impact of Sales Promotion on Profitability of the Pharmaceutical Industry of Pakistan: https://doi.org/10.5281/zenodo.16849977 - Simra Asghar; Dr. Muhammad Muzammil; Usama Bin Zarar (`, 2025)
This study investigates the influence of sales promotion strategies on the profitability of Pakistan’s pharmaceutical sector, a highly competitive and regulated market. Using a quantitative research design, secondary data from 100 pharmaceutical firms was analyzed to examine key variables promotion frequency, discounts, advertising spending, sales volume, and customer acquisition rate while incorporating control variables such as firm size, market competition, and regulatory environment. Regression and moderation analyses revealed that customer acquisition significantly enhances profitability, while promotional frequency, discounts, and advertising have positive but statistically insignificant effects. Larger firms and competitive markets benefit more from promotions, whereas stringent regulatory environments enhance trust but can reduce promotional impact. The findings underscore the importance of aligning sales promotion strategies with organizational capacity, market dynamics, and regulatory frameworks. Targeted advertising, strategic discounting, and high-value customer acquisition emerged as critical for sustainable growth. The study offers practical insights for managers and policymakers to design cost-effective, regulation-compliant promotional campaigns that strengthen market position and profitability. Keywords: Sales Promotion, Profitability, Pharmaceutical Industry, Pakistan, Customer Acquisition, Advertising Effectiveness, Strategic Discounting, Firm Size, Market Competition